Review of Doris L. Payne and Shahar Shirtz (eds.) 2015. Beyond Aspect: The expression of discourse functions in African Languages. Amsterdam/Philadelphia: John Benjamins [TSL 109], Pp. vii, 321 - (:unkn) unknown (My University, 2012)
This volume presents a series of corpus-based studies analyzing the various grammatical devices used to express discourse functions and to structure narratives in some ten African languages. Thanks to the editors’ effort in setting up comparative concepts, the scope of this book doubtlessly goes far beyond African linguistics and should interest descriptive linguists, typologists, as well as specialists of discourse studies. The book opens with an introductory and synthetic chapter by the editors. Then the nine following articles, devoted each to studies on particular languages, are ordered along language families (or phyla) of Africa.All together, the studies in this volume lead to a much refined view of the role of grammatical devices for structuring narratives. In particular, the storyline advancement appears to result from the co-occurrence of several features involving perfectivity and also verb types and information structure. Moreover, the structure of narratives follows recurring patterns accounting for the distribution of the various verbal forms in narratives, and indicating remarkable strategies for packaging the narrative event structure in most African languages. In this view, Cognitive Semantics and Mental Spaces have proved to provide very useful tools for approaching the ‘paradox of clausal grammar’ (Givón 1998) by relating TAM markers (clausal scope) with situations or Mental Spaces corresponding to portions of text (discourse scope), thus delineating the discourse structure and the speaker’s going back and forth between narrative and metanarrative spaces. Furthermore, the conjoint use of comparative concepts such as Main Event Line opens up the possibility of a typology of the expression of discourse functions. In these respects, this book may herald a breakthrough in the study of the grammar-discourse interface.
Keywords: African Research